Non contact tonometry synchronized with cardiac rhythm and its relationship with blood pressure - Queirós, A. (2006)
Purpose: The main objectives of this study were to determine the differences between non-synchronized intraocular pressure (IOP_N) and intraocular pressure readings synchronized with cardiac pulse and try to determine if these parameters are related to blood pressure values. Methods: One hundred and sixty-five right eyes from 165 volunteers (107 females, 58 males) aged from 19 to 73 years (mean ± S.D., 29.93 ± 11.17) were examined with the Nidek NT-4000, a new non-contact tonometer that allows the measurement of IOP synchronized with the cardiac rhythm. IOP measurements in the four different modes of synchronization were taken in a randomized order. Three measures of each parameter were taken and then averaged. The blood pressure was determined three times with a portable manometer and mean values of systolic and diastolic pressure and the pulse rate were computed. Mean arterial pressure (MAP) was determined as being 1/3 of systolic plus 2/3 of diastolic blood pressure. Results: The mean ± S.D. values for the standard intraocular pressure (IOP_N: 14.76 ± 2.86), intraocular pressure in the systolic instant or peak (IOP_P: 14.99 ± 2.85), intraocular pressure in the middle instant between heartbeats or middle (IOP_M: 14.68 ± 2.76), and intraocular pressure in the diastolic instant or bottom (IOP_B: 13.86 ± 2.61) were obtained. The IOP_P was higher than the remaining values. A significant difference in mean IOP existed between IOP_B and the remaining modes of measuring (p < 0.05). Differences were statistically significant for all pair comparisons involving IOP_B. Arterial blood pressure values were systolic 125.5 ± 14.22, diastolic 77.7 ± 8.38 and MAP 93.64 ± 9.44 mmHg. The pulse rate was 77.3 ± 12.6 beats per minute. Except for the MAP (p = 0.025) there was no significant correlation between different IOP values and systolic or diastolic blood pressure, or pulse rate. Conclusions: NT-4000 is able to differentiate IOP values when synchronized with the cardiac rhythm and those differences are expected to be within a range of ±2.5 to ± 3.0 mmHg. IOP_B seems to be the parameter whose value differs from the non-synchronized and the remaining synchronized parameters in a significant way. Other than a weak association with MAP, no significant correlation between IOP and BP was found. The measurements of IOP readings for the three modes are consistent with timings during the cardiac cycle and IOP pulse cycle.